Rapid Biodegradable Ionic Aggregates of Polyesters Constructed with Fertilizer Ingredients - Lee, Hyun Ju; Cho, Woo Yeon; Lee, Hong Cheol; Seo, Yeong Hyun; Baek, Jun Won; Lee, Pyung Cheon; Lee, Bun Yeoul (Journal of the American Chemical Society, 2022)
Synthetic biodegradable polyesters tend to undergo slow biodegradation under ambient natural conditions and, hence, have been rejected or even banned recently in ecofriendly applications. Here, we demonstrate the preparation of polyesters exhibiting enhanced biodegradability, which were generated through a combination of old controversial macromolecules and aggregate theories. H3PO4-catalyzed diacid/diol polycondensation afforded polyester chains bearing chain-end -CH2OP(O)(OH)2and inner-chain (-CH2O)2P(O)(OH) groups, which were subsequently treated with M(2-ethylhexanoate)2(M = Zn, Mg, Mn, and Ca) to form ionic aggregates of polyesters. The prepared ionic aggregates of polyesters, which were constructed with fertilizer ingredients (such as M2+and phosphate), exhibit much faster biodegradability than that of the conventional polyesters under controlled soil conditions at 25 °C, while displaying comparable or superior rheological and mechanical properties.
Keywords: Ambients; Biodegradable polyesters; Chain bearings; Chain-ends; Eco-friendly; Ionic aggregates; Natural conditions; Polycondensations; Polyester chains; Slow biodegradation